2017
DOI: 10.3390/ijms18010173
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Phospholipids from Colostrum, Milk and Dairy By-Products

Abstract: Milk is one of the most important foods for mammals, because it is the first form of feed providing energy, nutrients and immunological factors. In the last few years, milk lipids have attracted the attention of researchers due to the presence of several bioactive components in the lipid fraction. The lipid fraction of milk and dairy products contains several components of nutritional significance, such as ω-3 and ω-6 polyunsaturated fatty acids, CLA, short chain fatty acids, gangliosides and phospholipids. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 114 publications
(213 reference statements)
1
50
0
1
Order By: Relevance
“…The major health benefits reported from bovine milk PL and sphingolipids (review) are inhibition of colon cancer, anticholesterolemic and hypolipidaemic effects, anti‐inflammatory activity, improving the infant brain and cognitive development, as well as possible antiviral and antibacterial effects . These effects are illustrated by some recent studies, as shown in Table .…”
Section: Implication Of the Milk Lipid Fractions On Human Healthmentioning
confidence: 99%
“…The major health benefits reported from bovine milk PL and sphingolipids (review) are inhibition of colon cancer, anticholesterolemic and hypolipidaemic effects, anti‐inflammatory activity, improving the infant brain and cognitive development, as well as possible antiviral and antibacterial effects . These effects are illustrated by some recent studies, as shown in Table .…”
Section: Implication Of the Milk Lipid Fractions On Human Healthmentioning
confidence: 99%
“…Glycerophospholipids comprise a glycerol moiety with two fatty acids esterified at positions sn-1 and sn-2 and a hydroxyl group at sn-3 position, linked to a phosphate group and a polar moiety [1]. The molecular structure of the latter determines the types of glycerophospholipids, namely phosphatidylcholine (PC), phosphatidylserine (PS), phosphatidylethanolamine (PE), phosphatidylinositol (PI), phosphatidyl-glycerol (PG), and phosphatidic acid (PA) [2]. Sphingolipids consist of a sphingosine backbone (2-amino-4-octadecene-1,3-diol) connected to a fatty acid via an amide bond and a polar head.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, milk phospholipid liposomes were applied to improve the storage stability of encapsulates (Gulseren and Corredig, 2013), the encapsulate solubility and encapsulation efficiency Liu et al, 2012) and the bioavailability of encapsulate (Maswadeh et al, 2015), showing better efficiency than soy lecithin (Liu et al, 2012). Furthermore, in terms of biological effects, several review papers have summarized various health benefits of milk phospholipids, with emphasis on therapeutic aspects (Castro-Gómez et al, 2015), infant's gut development and cognitive functions (Ortega-Anaya and Jimenez-Flores, 2018), and physiological functionalities (Verardo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%